(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
• يعتبر المقطع الجمدي واحداً من أهم الإجراءات وأصعبها والتي ينجزها طبيب التشريح المرضي، بالتعاون مع الجرّاح. • الاستطبابات الأكثر شيوعاً للمقطع الجمدي هي:1) معرفة وجود وطبيعة الآفة في الثدي. 2 ) لمعرفة كفاية العمل الجراحي.3) لمعرفة فيما إذا كان النسيج المأخوذ كافياً للتشخيص. 4) الاستطباب الرابع وهو نادر نسبياً يجرى عند المرضى القلقين جداً والذين يصرون على النتيجة السريعة.5) الحصول على نسج من الأورام الخبيثة لدراسة مستقبلات الأستروجين والبروجسترون. • كان الاستطباب الأكثر شيوعاً في دراستنا هو تأكيد التشخيص للحالات المشبوهة بالخباثة إثر إجراءF N AC أو للكتل المجسوسة في الثدي. • أجريت الدراسة في مشفى الأسد الجامعي وفي الوحدات المهنية الخاصة على 40حالة خلال الفترة الواقعة بين 2000-2005: 1- كانت نسبة الدقة للمقطع الجمدي في دراستنا 85% (6 حالات من السلبية الكاذبة).2-في دراستنا كانت نسبة الإيجابية الكاذبة صفر.3-5 حالات شخصت على أنها غدوم ليفي سليم، أي بنسبة12.5%.4- حالتين شخصت على أنهما تبدل ليفي كيسي، أي بنسبة 5%.5-من بين الحالات الخبيثة (25حالة)، أي ما نسبته62.5% شخصت سرطان قنوي مرتشح بالمقطع الجمدي.6- وحالتين بنسبة 5% شخصتا سرطان لبي. The frozen section is one of the most important and difficult procedures that the pathologist performs during his practice. It requires experience, knowledge of clinical medicine, the ability to make quick decisions under pressure, good judgment at the end. The most common purposes of a frozen section are: 1) To know the presence and the nature of lesion. 2) To know the adequacy of surgical operation. 3) To know whether the tissue obtained contains diagnosable material or whether additional sampling is indicated. 4) The fourth and rare indication is in the highly anxious patient who insists on an expedited decision. 5) To obtain fresh material from malignant lesions for measurement of estrogen and prostergrone receptors. This study was performed in the special clinical units at AL-Assad University Hospital in Lattakia between 2000-2005. The most common indication of the breast frozen section in our study was to confirm the diagnoses of the suspicious lesions after (FNAC) performing, and of the palpable masses in the breast: • There wwere (40) cases. • The accuracy rate of the frozen section of the breast was (85%) [(16) cases false negative]. • The percentage of false positive frozen section diagnoses of the breast lesions was (0). • 5 cases were diagnosed as benign fiboadenoma (12.5%). • 2 cases were diagnosed as fibrocystic change (5%). • Among malignant cases, (25) cases were diagnosed as infiltrating ductal cancer (62.5%) and (2) cases were diagnosed as medullary cancer.